Repliek op Buyst en Lefebvre - Klemann, H.A.M. (BMGN - Low Countries Historical Review, 2004)
Reaction to Buyst and Lefebvre I only partly agree with Buyst and Lefebvre’s contention that I am no longer interested in treating the problems of collaboration and resistance as a key subject in World War II history. I oppose only a historiography in which moral answers are given to the question on why resistance was limited and adaptation common in the early years of the German occupation in the Netherlands. To answer this question, it is better to look for concrete differences between the Netherlands and other Western European countries. Its economic history can provide such an answer. In the Netherlands, the early years of the German occupation represented a period of economic welfare. As a result of the opening of the German market after a period of almost 10 years of German economic isolation, and as a result of enormous German orders, the Dutch economy flourished from July 1940 until late 1941. It ended the period of pre-war depression and mass unemployment. Together with the well-organised distribution of food, this economic boom may not have resulted in an outright acceptance of the occupation, but it at least made it easier for the population to accept what seemed to be inevitable anyway. Buyst and Lefebvre do not agree with the way I calculate from the new series of the national income, which showed a very limited decline, and available national income, which showed a dramatic decline from 1942 onwards, by subtracting the German withdrawals of goods and services from the Dutch economy from the national income. In their opinion, only income transfers without compensation should be subtracted from national income to compute available national income. I agree with this, but do not believe that the Germans gave any compensation for their withdrawals. Of course, Buyst and Lefebvre are right; Dutch companies were paid by the Germans for their orders, but the money with which they paid was illegally taken from the Dutch treasury or acquired by inflating the Dutch money supply without compensation. This is important because it makes clear that on the one hand Dutch national income did not decline — as was thought until only recently — by almost 50% between 1938 and 1944, but only by 15%. Nevertheless, Dutch society rapidly declined into acute poverty because the occupier took up to 45% of the national income without compensation. As a result, available national income declined by more than 50%. Nor do Buyst and Lefebvre like the way I explained my calculations: They think I am too cryptic. My reasons for this were because I believe that the book is important not only to economic historians but to everyone interested in World War II and I wanted to prevent it from only circulating among a limited number of economic historians. In fact, most of my calculations had already been published earlier. Of course, they are correct in their assertion that the decision to make the book available to a wider audience makes it hard to find all the explanations of the calculations. The explanations are present, however they tend to be brief and are scattered throughout the book. To compensate for this, I will publish all the calculations on the web, as soon as possible. This response is part of the discussion forum ’Nederland 1938-1948’ (Hein Klemann).